Emotion and Islamic Hagiology: A Post-taxonomic Approach - Yep, Stephanie (Method & theory in the study of religion, 2023)
The study of emotion in Islamic hagiology remains largely uninterrogated, as visible in elliptical descriptions that classify particular texts, bodily gestures, or utterances as “emotive.” I advocate for a shift from taxonomic approaches to emotion to a focus on function in narrative hagiographies. I argue that emotion provides a rich analytic category for understanding the dynamic relationship between texts and bodies in the hagiographical process, as well as the multiplicity of bodies that are involved or implicated. To illustrate this framework, I provide readings of narratives in the sīra (biographies of Muḥammad) which depict bodily manifestations of awe when in Muḥammad’s presence. Endorsing the position that the hagiographical process is constantly under negotiation, these analyses reveal that emotional practices are crucial to understanding the relationality between exemplary persons, biographers, characters, and readers.